Interrupted aortic arch by multi-detector computed tomography angiography: A case report with radiological review - Sanjay M Khaladkar; Kuldip P Chaudhary; Rajesh S Kuber; Anubhav Kamal (Wolters Kluwer Medknow Publications, 2016)
Interrupted aortic arch (IAA) is a rare congenital vascular malformation, which is defined as lack of luminal continuity, between the ascending and descending thoracic aorta. Many times it is associated with various congenital cardiac anomalies. Early diagnosis is mandatory to assess the patient condition and to plan medical and surgical treatment. Traditionally, chest X-ray, echocardiography, and conventional catheter angiography are the imaging tools being used. Multi-detector computed tomography (MDCT) can accurately diagnose and characterize the various forms of IAA and associated cardiac defects. We report a case of 8-year-old male child detected to have Type A IAA on MDCT with an associated ventricular septal defect and patent ductusarteriosus.